HIKAYAT MALIM DEMAN: ANALISIS INTERTEKSTUAL - , YASWINDA FERONICA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Hikayat Malim demam has been classified as a saga coming up from classical Malay literature and being popular for its aesthetic aspect which mostly narrates a solace tale. Hikayat Malim Damam brings a tale of a man in the earth who marries an angel as he stole her clothes or wings. The tale of Malim Demam has spread out over Indonesian archipelago and has lived settled in Malay literature up to this time. Till this research has been conducted, there are no other researches taking Hikayat Malim Demam as its material object. Similar tales of Malay literature used as supporting data in the research are Legenda Jaka Tarub, Legenda Lahilote, and Legenda Telaga Bidadari. These four tales are suspected to have an inter-textual relation leading to their similarity and differences in the intrinsic elements of story structure. It is in line with Julia Kristevaâs opinion stating that text is a mosaic of citations, absorption and transformation of other texts. Based on this argument, the research explains intertextual forms of Hikayat Malim Damam with Legenda Jaka Tarub, Lahilote, and Telaga Bidadari. Moreover, the research also explains the function and meanings of Hikayat Malim Damam as classical Malay work and similar tales as well as a story based on socio-cultural of its supporting society. The research employs three methods namely the method of selecting text, data collecting method and data analysis method. In the method of text selection level, the works chosen are works which are the nearest and easiest to access.Then, data collecting step is carried out by reading all tales inter-textually. The collected data then are all information related to and suspected as story inter-textual forms. The classified data is analyzed then using inter-textual method proposed by Julia Kristeva by highlighting the aesthetic values in line with Braginskyâs theory. Based on data analysis result, the research proves an inter-textual relation between Hikayat Malim Demam and Legenda Jaka Tarub, Lahilote, and Telaga Bidadari. The intertextual relation founded appears as similarities and differences of story structure such as plot, motive, characterization, setting and theme. Moreover, the research also shows that Hikayat Malim Demam complies the function of classical Malay literature and and the meaning of each story based on socio-cultural of supporting society.